Lecturers’ Perception of Content Language Integrated Learning in Teaching International Class at Universitas Negeri Padang - Delarosa, Adelia; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
Content Language Integrated Learning (CLIL) is an educational approach that is appropriate to be implemented in international class since the aims are to help the students mastering the content subject and the target language. This study aimed to find the lecturers’ perception of the benefits and the obstacles in implementing CLIL approach in international class at Universitas Negeri Padang. The method used in this study was survey research that used closed-ended questionnaire which consists of 47 items of statements and open-ended questionnaire which consists of 8 questions to collect the data. The samples of this study were 18 lecturers who teach in different international classes at Universitas Negeri Padang. The findings showed that mostly the lecturers have very positive perception that CLIL provides many benefits for themselves. CLIL improve lecturers’ language proficiency, lecturers’ attitudes, lecturers’ understanding on the subject, and lecturers’ cultural awareness. In addition, the results of this study showed that most of the lecturers do not have big problems that can obstruct CLIL implementation. However, there were still lecturers who have problems in implementing CLIL approach related to the lesson planning, materials development, understanding on the target language and communication skills.